Induction of apoptosis by IFNγ in human neuroblastoma cell lines through the CD95/CD95L autocrine circuit - Bernassola, Francesca; Herr, Ingrid; Krammer, Peter H. (Cell death and differentiation, 1999)
The CD95 (APO-1/Fas) system can mediate apoptosis in immune cells as well as in tumour cells, where it may contribute to tumour immune-escape. On the other hand, its induction by anticancer drugs may lead to tumour reduction. Interferonγ (IFNγ) increases the sensitivity of tumour cell lines to anti-CD95 antibody-mediated apoptosis. We describe induction of apoptosis by IFNγ through the expression of CD95 and its ligand (CD95L) in human neuroblastoma cell lines. Neuroblastoma cells showed low constitutive expression of CD95 and CD95L. Subsequent to IFNγ-modulated increase in CD95 and CD95L mRNA as well as protein levels, apoptosis was observed. Our results demonstrated that cytokine-mediated apoptosis was mediated through the activation of the CD95/CD95L autocrine circuit since: (i) cell death occurred following CD95/CD95L expression and correlated with CD95 and CD95L expression levels, (ii) failed to occur in a clone which weakly upregulated CD95 and lacked CD95L induction after IFNγ stimulation, (iii) was at least partially inhibited by using blocking F(ab′)2 anti-CD95 antibody fragments and the recombinant Fas-Fc protein, that prevented the interaction between CD95 and CD95L. The intracellular molecular mechanisms elicited by IFNγ are clearly highly complex, with several signalling pathways being activated, including the CD95 system. These findings suggest that IFNγ may have a significant potential in the therapy of neuroblastoma in vivo.
Gesehen am 23.04.2021